Cause of The Low Positivity of Blood Culture in Septic Patients - Yana, Krishna; Alisjahbana, Bachti; Hartantri, Yovita (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Sepsis due to bacterial infection is one of the main causes of high disease morbidity and mortality. Management of sepsis, the detection of bacteriemia by examination of blood cultures has an important role, but until now the positivity of blood culture results at Hasan Sadikin Hospital (RSHS) is still low (13.45%). The purpose of this study was to determine profile the causes of low positivity of blood culture results in sepsis patients in RSHS. Methods. A cross sectional study was conducted on sepsis patient treated in Emergency Un it (ER) and inpatient of Hasan Sadikin hospital Internal Medicine from December 2016 until April 2017. This study collects patient clinical information, laboratory, history Administration of antibiotics, and techniques of examination of bacterial blood cultures in sepsis patients. Results. During the study period 179 subjects were obtained. The subject mainly uses the Health Guarantee Agency (BPJS) for financing. The positivity of blood cultures was found to be 24%. The mean leukocyte count on positive blood culture results was 18,100 / mm3 and there were 79.07% cultures with Neutrofil Limfosit Count Ratio (NLCR) >10. The time for taking blood cultures is mainly done at> 6 hours after admission. The number of blood cultures is taken at least once. The amount of blood volume in each culture tube is mostly 5 cc. Taking blood cultures is mainly carried out by competent nurses who have not received blood culture taking training. Conclusions. The positive results of blood culture in septic patients in RSHS are still low. Taking blood cultures should be carried out in accordance with the guidelines, which consist of not giving antibiotics before taking blood culture, taking blood time at admission, the number of blood taken for culture >1 time, the amount of blood volume in a culture tube is at least 10 cc, use 2 types of antiseptics, the use of antiseptics on culture bottle caps, the time lag between antiseptic action and blood collection for culture. It is necessary to monitor the factors that influence the positivity of blood cultures in septic patients. Researchers also recommend training and policy improvements to improve blood culture positivity.